Microencapsulation and Fermentation of Lactobacillus acidophilus LA-5 and Bifidobacterium BB-12 - Maryam Yari; Jamshid Fooladi; Mohammad Ali Kargar Motlagh (Applied Food Biotechnology, 2015)
Because of poor survival of probiotic bacteria, microencapsulation evolved from the immobilized cell culture technology used in the biotechnological industry. Two probiotic strains, Bifidobacterium (BB-12) and Lactobacillus acidophilus (LA-5) were immobilized in calcium alginate by extrusion method. Encapsulation parameters and efficacy of this method were evaluated. Growth factors of these two bacteria were also measured by culturing in 10-L fermenter. Growth curves were obtained with respect to optical density and dry biomass weight. Encapsulation yield was over than 60% in each experiment. Scanning electron microscopy (SEM) of Entrapment of cells in alginate matrix and cross-sections of dried bead were obtained and illustrated. Bifidobacterium have been shown better biotechnological properties.